2010
DOI: 10.1002/chem.200902494
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Water Dissociation in Surface‐Modified BaCoxFeyZr1−xyO3−δ Hollow‐Fiber Membrane Reactor with Improved Oxygen Permeation

Abstract: A porous perovskite BaCo(x)Fe(y)Zr(0.9-x-y)Pd(0.1)O(3-delta) (BCFZ-Pd) coating was deposited onto the outer surface of a BaCo(x)Fe(y)Zr(1-x-y)O(3-delta) (BCFZ) perovskite hollow-fiber membrane. The surface morphology of the modified BCFZ fiber was characterized by scanning electron microscopy (SEM), indicating the formation of a BCFZ-Pd porous layer on the outer surface of a dense BCFZ hollow-fiber membrane. The oxygen permeation flux of the BCFZ membrane with a BCFZ-Pd porous layer increased 3.5 times more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Similar results were reported in 75 wt % Ce 0. 8 Figure 10. Arrhenius plots of the oxygen permeation fluxes through 40NFO-60CGO dual phase membranes (for the experimental conditions see Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported in 75 wt % Ce 0. 8 Figure 10. Arrhenius plots of the oxygen permeation fluxes through 40NFO-60CGO dual phase membranes (for the experimental conditions see Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oxygen permeation flux can be further improved if the permeated oxygen can be fast consumed on the permeate side of perovskite membrane. For example, Jiang et al (2010b) reported that, the oxygen permeation flux of a perovskite BaCo x Fe y Zr 1−x−y O 3−δ (BCFZ) hollow-fiber membrane increased from 3.3 to 8 cm 3 min −1 cm −2 when methane was fed on shell side at 875°C. Lobera et al (2012) further observed that when dilute methane was used as sweep gas in a perovskite Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF) membrane reactor, the logarithm of oxygen partial pressure gradient increased from 1.16 to 4.02, resulting in a 2.5-fold increase of oxygen permeation flux.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this concept are: (i) the oxygen permeation flux can be increased by the decreased oxygen partial pressure on the permeate side; (ii) syngas can be produced in this operation, which can be applied in the production of oxygenates (methanol) and hydrocarbons (diesel), as well as the hydrogen production through CO + H 2 O ? H 2 + CO 2 , the water gas shift reaction operated at relatively low temperatures [202][203][204]. Fig.…”
Section: Water Splitting To Hydrogenmentioning
confidence: 99%
“…At 950°C, 70% CH 4 conversion and 60% CO selectivity with the hydrogen rate of 3.5 ml/min cm 2 was obtained. In our recent work [203], a porous catalyst layer of BaCo x Fe y Zr 0.9ÀxÀy Pd 0.1-O 3Àd (BCFZ-Pd) was coated on the surface of BCFZ hollow fiber membrane. The production rate of hydrogen raised to 2.1 ml/ min cm 2 at 950°C, which was about three times of that with blank BCFZ membranes.…”
Section: Water Splitting To Hydrogenmentioning
confidence: 99%